2016
DOI: 10.1108/jpcc-01-2016-0002
|View full text |Cite
|
Sign up to set email alerts
|

More than a mentor

Abstract: If you would like to write for this, or any other Emerald publication, then please use our Emerald for Authors service information about how to choose which publication to write for and submission guidelines are available for all. Please visit www.emeraldinsight.com/authors for more information. About Emerald www.emeraldinsight.comEmerald is a global publisher linking research and practice to the benefit of society. The company manages a portfolio of more than 290 journals and over 2,350 books and book series … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
21
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(25 citation statements)
references
References 68 publications
2
21
0
2
Order By: Relevance
“…Staff who have a sense of belonging to the group, and feel valued as part of the team, are socially connected. Evidence points to this being a predictor of resilience, which may mitigate the effects of stress and burnout (Hurley et al, 2014;Seppala, Hutcherson, Nguyen, Doty, & Gross, 2014;Struyve et al, 2016). This collective approach not only benefits staff but also impacts significantly on the care of patients and their families (Hall, Johnson, Watt, Tsipa, & O'Connor, 2016;Panagioti, Geraghty, & Johnson, 2018).…”
Section: The Impact Of Team Resiliencementioning
confidence: 99%
“…Staff who have a sense of belonging to the group, and feel valued as part of the team, are socially connected. Evidence points to this being a predictor of resilience, which may mitigate the effects of stress and burnout (Hurley et al, 2014;Seppala, Hutcherson, Nguyen, Doty, & Gross, 2014;Struyve et al, 2016). This collective approach not only benefits staff but also impacts significantly on the care of patients and their families (Hall, Johnson, Watt, Tsipa, & O'Connor, 2016;Panagioti, Geraghty, & Johnson, 2018).…”
Section: The Impact Of Team Resiliencementioning
confidence: 99%
“…A social take on teachers' first years in the profession Crucial in influencing these teachers' job attitudes, and their decisions to remain in or leave the job, are the professional relationships with and support from their colleagues (Fox and Wilson 2015;Struyve et al 2016). Specifically, collegial support is found to be important to help beginning teachers deal with experienced difficulties in the first years of practice (Papatraianou and Le Cornu 2014;Struyve et al 2016). Conversely, without support, beginning teachers often quit their job (Rippon and Martin 2006).…”
Section: Theoretical Framework Beginning Teachers' Job Attitudesmentioning
confidence: 99%
“…Several studies (e.g. Ibarra and Andrews 1993;Struyve et al 2016) have found that being socially tied and as such being central in the team, positively influences job attitudes and employees' decisions to remain in the profession.…”
Section: Theoretical Framework Beginning Teachers' Job Attitudesmentioning
confidence: 99%
See 2 more Smart Citations